Characteristics and Prognosis of Allergic Proctocolitis in Infants. Issue 1 (July 2015) - Kaya, Aysenur; Toyran, Muge; Civelek, Ersoy; Misirlioglu, Emine; Kirsaclioglu, Ceyda; Kocabas, Can N.
ABSTRACT Objectives: The dietary protein proctocolitis, also known as allergic proctocolitis (AP), is characterized by the presence of mucoid, frothy, and bloody stools in an otherwise healthy infant. The aim of this study was to describe a group of children with AP, diagnosed according to the criterion-standard method, food challenge to provide clinicians with more information on typical presentation, and an overview on nutritional management strategies and prognosis. Methods: We collected data on infants with AP in our allergy and gastroenterology outpatient clinics. Any other conditions that may cause bloody diarrhea were ruled out. Skin prick tests and atopy patch tests were performed for diagnosis, and patients were studied for resolution. To the patients whose rectal bleeding did not recover with oligoantigenic maternal diet in addition to amino acid–based formula, endoscopic evaluation was performed to confirm the diagnosis and to exclude other reasons of rectal bleeding. Results: Sixty patients were diagnosed as having AP. The age of onset was 1.7 ± 1.32 months. All of the patients were triggered by milk, 6.6% with milk and egg, 3.3% with milk and chicken, 1.7% with milk and wheat, 1.7% with milk and potato, and 3.3% had multiple food allergy. 53.3% (n = 32) acquired tolerance by age 1, 25.0% (n = 15) by 2 years, 5% (n = 3) by 3, and 1.7% (n = 1) by 4 years. Conclusions: Milk was a triggering factor for all of the patients. Resolution of AP is usually within 1 year but symptoms of some patients may continue even longer. An extension of the follow-up period is required according to our study.